Plasmonics for advance single-molecule fluorescence spectroscopy and imaging in biology - Zaza, Cecilia; Simoncelli, Sabrina (Frontiers in Photonics, 2022)
The elucidation of complex biological processes often requires monitoring the dynamics and spatial organization of multiple distinct proteins organized on the sub-micron scale. This length scale is well below the diffraction limit of light, and as such not accessible by classical optical techniques. Further, the high molecular concentrations found in living cells, typically in the micro- to mili-molar range, preclude single-molecule detection in confocal volumes, essential to quantify affinity constants and protein-protein reaction rates in their physiological environment. To push the boundaries of the current state of the art in single-molecule fluorescence imaging and spectroscopy, plasmonic materials offer encouraging perspectives. From thin metallic films to complex nano-antenna structures, the near-field electromagnetic coupling between the electronic transitions of single emitters and plasmon resonances can be exploited to expand the toolbox of single-molecule based fluorescence imaging and spectroscopy approaches. Here, we review two of the most current and promising approaches to study biological processes with unattainable level of detail. On one side, we discuss how the reduction of the fluorescence lifetime of a molecule as it approaches a near thin metallic film can be exploited to decode axial information with nanoscale precision. On the other, we review how the tremendous progress on the design of plasmonic antennas that can amplify and confine optical fields at the nanoscale, powered a revolution in fluorescence correlation spectroscopy. Besides method development, we also focus in describing the most interesting biological application of both technologies.